2005
DOI: 10.1097/01.mlg.0000150702.28451.35
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprotegerin in the Inner Ear May Inhibit Bone Remodeling in the Otic Capsule

Abstract: OPG, a potent inhibitor of osteoclast formation and function, is expressed at high levels within the inner ear and is secreted into the perilymph and the surrounding bone and may serve to inhibit active bone remodeling within the otic capsule, especially immediately adjacent to the cochlea. By this means, the cochlear soft tissue may control the nature of the surrounding petrous bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
105
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(113 citation statements)
references
References 24 publications
6
105
0
Order By: Relevance
“…We recently found that expression of OPG also best characterizes the wild-type otic capsule (unpublished data). Our previous work showed that OPG plays an important role in the inhibition of otic capsule remod-eling [Zehnder et al, 2005], and that the otic capsule of the OPG knockout mice undergoes abnormal remodeling that closely resembles otosclerosis [Zehnder et al, 2006]. Because we did not observe active remodeling in the otic capsule of Mov13 mice, it is not surprising that expression levels of OPG remained high in the Mov13 otic capsule, thus contributing to the selection of OPG as a gene that is highly characteristic of the otic capsule.…”
Section: Discussionmentioning
confidence: 99%
“…We recently found that expression of OPG also best characterizes the wild-type otic capsule (unpublished data). Our previous work showed that OPG plays an important role in the inhibition of otic capsule remod-eling [Zehnder et al, 2005], and that the otic capsule of the OPG knockout mice undergoes abnormal remodeling that closely resembles otosclerosis [Zehnder et al, 2006]. Because we did not observe active remodeling in the otic capsule of Mov13 mice, it is not surprising that expression levels of OPG remained high in the Mov13 otic capsule, thus contributing to the selection of OPG as a gene that is highly characteristic of the otic capsule.…”
Section: Discussionmentioning
confidence: 99%
“…Bone remodeling within the otic capsule has been reported to be inhibited at or near the cochlea compared to the rest of the skeleton [Frisch et al, 1998[Frisch et al, , 2015Zehnder et al, 2005]. Zehnder et al [2005] demonstrated that osteoprotegerin (OPG), a powerful inhibitor of bone remodeling, was expressed at high levels within the soft tissue of the mouse cochlea and it was present in the perilymph at high concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Zehnder et al [2005] demonstrated that osteoprotegerin (OPG), a powerful inhibitor of bone remodeling, was expressed at high levels within the soft tissue of the mouse cochlea and it was present in the perilymph at high concentrations. Bone remodeling is tightly regulated by 3 cytokines: OPG, receptor activator of nuclear factor-κB (RANK), and RANK ligand (RANKL).…”
Section: Introductionmentioning
confidence: 99%
“…The RANK/RANKL/OPG signaling system that has recently been suggested to inhibit bone resorption and remodeling in the otic capsule [16,17] may act through the osteocytic lacunocanalicular network in perilabyrinthine bone [19] . Disruption of canaliculi and possibly even the osteocytic syncytium by MDx and larger microfissures might indeed interfere with signal transduction, counteract inhibiting signals and precipitate pathological bone remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…With the recognition of an inner ear signaling pathway [16,17] that inhibits perilabyrinthine bone remodeling to a mere 1% of the general rate [18] , otic capsular microfissures deserve renewed attention because these lesions are predicted by the virtual absence of bone remodeling and because they might disrupt the continuity of the lacunocanalicular porosity, affect the viability of the osteocytic network, interfere with perilabyrinthine antiresorptive signal transduction and consequently facilitate pathological capsular bone remodeling such as otosclerosis [19] .…”
Section: Introductionmentioning
confidence: 99%